PENGARUH KEBIJAKA N PEMERINTAH TERHADAP RESILIENCE UMKM DIMASA PANDEMIC COVID-19 - Iroh Rahmawati; Irna Maya Sari (Jurnal Bina Bangsa Ekonomika, 2024)
COVID-19 has had four main impacts on MSMEs and the informal sector.First, a decline in sales, second, limited supply  of raw materials, third, difficulty in paying loans, fourth, layoffs of employees, limited sales receipts make informal business actors try to reduce expenses, by reduce the amount of employee salaries.The purpose of this study is to find out how much government policy has an influence  on the resilience of MSMEs during the Covid-19 pandemic, especially in the city of Serang and to provide suggestions and policies to the government.  The research method used is simple linear regression. The results of this study show that government policies have an effect on  the resilience  of MSMEs during the Covid-19 pandemic in the city of Serang by 0.673 or 67.3%